Acute beneficial effects of a functional energy shot on cognitive performance and mood states during cognitively demanding task performance: a randomized, double-blind, placebo-controlled, crossover trial - O’Shea, Olivia K.; Lawley, Nathan; Azzopardi, Anna; Gutkowski, Allison; Niedziela, Michelle Murphy; Horn, Rachel; Kennedy, David O.; Adamson, Jason (Frontiers in Nutrition, 2025)
IntroductionFunctional beverages are increasingly popular but it is important to validate their purported effects through research. The aim of the current study was to investigate the effects of a new functional energy shot on cognitive performance and mood states in healthy adults, with a focus on measuring mental energy enhancement and attenuation of negative effects associated with extended performance of mentally demanding tasks.MethodsThis study was a randomized, double-blind, placebo-controlled, crossover trial. Thirty-seven healthy males and females, aged 18–30 years, consumed a functional energy shot (Ryde: Energize) or placebo on separate testing occasions one-week apart. Participants completed cognitive and mood assessments pre-dose, and then 30 minutes post-dose over the course of approximately 2 hours. The functional energy shot contained caffeine, ginseng, vitamins and taurine, while the placebo shot was matched for flavor but did not contain these additional ingredients.ResultsUse of the functional energy shot was associated with significant improvements over placebo in cognitive performance, as measured by the Cognitive Demand Battery, with enhanced global performance, task-specific accuracy and speed across repeated assessments. Additionally, the shot mitigated negative effects associated with extended cognitive tasks, reducing perceived mental fatigue and increasing perceived alertness and energy. Working memory tasks showed faster performance post-consumption, and mood assessments revealed positive effects on vigor, fatigue and overall mood disturbance.DiscussionThese results indicate wide cognitive and mood effects of this functional energy shot, potentially attributable to synergistic combination of active ingredients.Clinical trial registrationclinicaltrials.gov, identifier NCT06384586.